PENETAPAN USIA DEWASA CAKAP HUKUM BERDASARKAN UNDANG-UNDANG DAN HUKUM ISLAM - Nurkholis Nurkholis (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Differences in adult age or child's age limits on Indonesian laws and regulations raise questions about which limitations should be used. As contained inPasal 330 KUHPerdata, Age 21 Th or already married,           Pasal 9 (1) Kompilasi Hukum Islam, age 21 years, Pasal 47 (1) UU Perkawinan, age 18 years, Pasal 1 (1) UU Perlindungan Anak, age 18 years, Pasal 1 ayat (2) UU. Tenaga Kerja, age 18 years old; and         Pasal 1 (8) UU Pemilu, 17 years or already married. In Islamic jurisprudence of adult age is someone who has until baligh period. Means reaching the age that one is religiously duty-bound; one is obliged to obey religious laws.Signs of religious puberty are: semen discharge, growth of coarse pubic hair, or reaching the specific age of puberty. By appearance of any of these signs, one is regarded as baligh (adult) and mukallaf (duty-bound).